Plant–microbiome interactions for sustainable agriculture: a review - Gupta, Rupali (Physiol Mol Biol Plants, 2021)
Plant–microbiome interactions are significant determinant for plant growth, fitness and productivity. Depending upon the specific habitat, plants' microbial communities are classified as the rhizo-, phyllo-, and endospheric regions. Understanding the plant microbiome interactions could provide an opportunity to develop strategies for sustainable agricultural practices. There is a necessity to decipher the complex structural and functional diversity within plant microbiomes to reveal its immense potential in agriculture. The plant microbiota harbors enormous microbial communities that defy analytical methodologies to study dynamics underlying plant microbiome interactions. Findings based on conventional approaches have ignored many beneficial microbial strains, which creates a serious gap in understanding the microbial communications along with the genetic adaptations, which favors their association with host plant. The new era of next generation sequencing techniques and modern cost-effective high-throughput molecular approaches can decipher microbial community composition and function. In this review, we have presented the overview of the various compartments of plants, approaches to allow the access to microbiome and factors that influence microbial community composition and function. Next, we summarize how plant microbiome interactions modulate host beneficial properties particularly nutrient acquisition and defense, along with future agricultural applications. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at. 10.1007/s12298-021-00927-1.